MODERASI ISLAM, UNTUK PERADABAN DAN KEMANUSIAAN - Fauzi, Ahmad (JURNAL ISLAM NUSANTARA, 2018)
The purpose of this article is to discuss the moderation of Islam for civilization and the humanity of the method used in qualitative research in the form of library research (Library Research), which is descriptive through logical analysis. While the technique used in lifting the data is by Book Research or library research. Because of the interpretation of the study, the data is taken from the Qur'an to check the validity of the analysis of the commentaries on Maktabah Syamilah. This article concludes that the moderation of Islam for civilization and humanity is a unified whole through a flexible teaching system, especially instilling character values can foster a tolerant attitude towards Indonesian plurality, a flexible teaching system through the design of humanistic theories is expected to be able to make humans who have a comprehensive civilization not only material aspects but also proficient in spiritual elements.